Neutrophil‐mediated enhancement of angiogenesis and osteogenesis in a novel triple cell co‐culture model with endothelial cells and osteoblasts - Herath, Thanuja D. K. (2020)
Repair and regeneration of critical‐sized bone defects remain a major challenge in orthopaedic and craniomaxillofacial surgery. Until now, attempts to bioengineer bone tissue have been hindered by the inability to establish proper angiogenesis and osteogenesis in the tissue construct. In the present study, we established a novel triple cell co‐culture model consisting of osteoblasts, endothelial cells, and neutrophils and conducted a systematic investigation of the effects of neutrophils on angiogenesis and osteogenesis. Neutrophils significantly increased angiogenesis in the tissue construct, evidenced by the formation of microvessel‐like structures with an extensive lattice‐like, stable tubular network in the co‐culture model. Moreover, neutrophils significantly induced the expression of pro‐angiogenic markers, such as VEGF‐A, CD34, EGF, and FGF‐2 in a dose‐ and time‐dependent manner. Subsequently, PCR arrays corroborated that neutrophils upregulate the important angiogenic markers and MMPs. Moreover, neutrophils also enhanced osteogenic markers, such as ALP, OCN, OPN, and COL‐1 compared with the controls. As shown by the osteogenic gene arrays, neutrophils significantly regulated major osteogenic markers such as BMP2, BMP3, BMP4, BMP5, TGF‐β2, RUNX2, and ECM proteins. Significantly higher mineralization was observed in triple cell co‐culture compared with controls. Foregoing data indicate that the triple cell co‐culture model can be used to stimulate the growth of microvasculature within a bone bioengineering construct to improve cell viability. Neutrophil‐mediated enhancement of angiogenesis and osteogenesis could be a viable, clinically relevant tissue engineering strategy to obtain optimal bone growth in defect sites, in the field of oral and maxillofacial surgery.